Revision of the Neotropical caddisfly genus Banyallarga (Trichoptera: Calamoceratidae) - Prather, Aysha L. (Zootaxa, 2004)
Systematics of the genus Banyallarga are reviewed. Illustrations, a generic diagnosis, and descriptions are provided for males and females. A new subgenus, Histricoverpa, is recognized. Nine previously described species are recognized: Banyallarga (Banyallarga) argentinica Flint, B. (B.) columbiana (Nav s), B. (B.) loxana (Nav s), B. (B.) vicaria (Walker) B. (B.) villosa (Nav s), B. (B.) yungensis Flint, B. (Histricoverpa) acutiterga (Denning and Hogue), B. (H.) fortuna (Resh), and B. (H.) mollicula (McLachlan). Eight species are described as new: B. (B.) penai (Peru), B. (H.) echinata (Peru), B. (H.) mexicana (Mexico), B. (H.) nica (Nicaragua), B. (H.) quincemil (Peru), B. (H.) sanchezi (Colombia), B. (H.) sylvana (Costa Rica, Nicaragua), and B. (H.) tapanti (Costa Rica). Banyallarga testacea is designated a synonym of B. (B.) vicaria and a neotype of B. testacea is designated to clarify the identity of the genus. The genus Loxinum, formerly considered a synonym of Banyallarga, is designated a synonym of Chimarrhodella (Philopotamidae).